'Christian radicalism' in the Church of England, 1957-1970 - Brewitt-Taylor, S; Samuel Brewitt-Taylor (2012)
This thesis is the first study of ‘Christian radicalism’ in the Church of England between 1957 and 1970. Radicalism grew in influence from the late 1950s, and burst into the national conversation with John Robinson’s 1963 bestseller, Honest to God. Emboldened by this success, between 1963 and 1965 radical leaders hoped they might fundamentally reform the Church of England, even though they were aware of the diversity of their supporting constituency. Yet by 1970, following a controversial turn towards social justice issues in the late 1960s, the movement had largely reached the point of disintegration. The thesis offers five central arguments. First, radicalism was fundamentally driven by a narrative of epochal transition, which understood British society in the late 1950s and early 1960s to be undergoing a seismic upheaval, comparable to the transition between the Middle Ages and the Renaissance. Secondly, this led radicals to exaggerate many of the social changes occurring in the period, and to imagine the emergence of a new social order. Radicals interpreted affluence as an era of unlimited technology, limited church decline as the arrival of a profoundly secular age, and limited sexual shifts as evidence of a sexual revolution. They effectively created the idea of the ‘secular society’, which became widely accepted once it was adopted by the Anglican hierarchy. Third, radical treatment of these themes was part of a tradition that went back to the 1940s; radicals anticipated many of the themes of the secular culture of the 1960s, not the other way round. Fourth, far from slavishly adopting secular intellectual frameworks, radical arguments were often framed using theological concepts, such as Christian eschatology. Finally, for all these reasons, Christian radicals made an original and influential contribution to the elite re-imagination of British society which occurred in the 1960s.